Simple Covalent Attachment of Redox‐Active Nitroxyl Radicals to Graphene via Diels‐Alder Cycloaddition. Issue 15 (17th May 2017) - Lazar, Ion‐Matei; Rostas, Arpad M.; Straub, Paula S.; Schleicher, Erik; Weber, Stefan; Mülhaupt, Rolf
Abstract : Nitroxyl‐radical functionalization of graphene, derived by solution exfoliation, via Diels‐Alder cycloaddition, enabling its use as redox‐active electrode material in organic energy storage devices. Time‐resolved electron paramagnetic resonance spectroscopy gives an interesting insight into the stability of the radical species during reaction. Combined with Raman spectroscopy, elemental analysis, and cyclic voltammetry, the success of the graphene functionalization can be proven. Abstract : Here, this study reports a novel single‐step preparation of graphene functionalized by redox‐active nitroxyl radicals, a promising electrode material, without the requirement of graphite oxidation. Key feature of this concept is the Diels‐Alder [4+2] cycloaddition of dispersed graphene (DG), which has been obtained by shear‐induced solution exfoliation of graphite and functionalized maleimides as dienophiles. The redox‐active organic radical 2, 2, 6, 6, ‐tetramethylpiperdinyl‐1‐oxyl (TEMPO) is covalently attached by cycloaddition of DG with either N ‐(1‐oxyl‐2, 2, 6, 6, ‐tetramethyl‐4‐piperidinyl)‐maleimide (TEMPO‐MI), or N ‐(2, 2, 6, 6‐tetramethyl‐piperidinyl)‐maleimide (TEMP‐MI), and subsequent oxidation. Successful product formation could be confirmed by high field Electron Paramagnetic Resonance (EPR) spectroscopy. Temperature‐dependent reaction monitoring by time‐resolved EPR in conjunction with Raman spectroscopy and elemental analysis results in an optimum cycloaddition temperature of 130 °C, at which 2.2 wt% TEMPO‐MI has been incorporated. However, owing to the limited thermal stability of TEMPO‐MI at temperatures above 100 °C, as again verified by EPR spectroscopy, the route via TEMP‐MI and subsequent oxidation is favored. Cyclovoltammetric evaluation of TEMPO‐functionalized graphene shows a reversible redox potential of +0.65 V as measured against Ag/AgCl, similar to that of TEMPO in solution. Hence, organic radical functionalized graphene derived by cycloaddition shows great potential for an easy production of electrodes that aim toward applications in organic energy storage devices.